Teacher’s Strategies in Teaching Contextual English at SMK N 1 Wadaslintang - Abdulloh Abdulloh; Abdul Abdul (Proceedings Series on Social Sciences & Humanities, 2023)
The objectives of this research are to find out the strategies used by the teachers in teaching contextual English, to find out the strategies aplied by the teachers in the classroom and to find out the strategies used by the teachers to improve the student’s enggagement in the classroom in merdeka curriculum by English Teachers of SMK Wadaslintang, Wonosobo Regency. The methodology of this reserach is qualitative. The data were collected through observation in the classroom, interview and questionaires. The results of the research shows that teachers use some teaching strategies which accomodate contextual English like Problem based learning. The teachers use the syntact of CTL, relating, experiencing, applying, cooperating and transfering even though it has another names. The teachers agree that the strtategies can engage student’s in participating actively in the classroom.